Forest genetic resources conservation and management: In plantations and genebanks (ex situ) : Vol. 3 - International Plant Genetic Resources Institute (2004)
This guide is the third volume of a series of three that deal with the conservation of forest (trees and shrubs) genetic resources. This volume addresses technical requirements, and some applied approaches and experiences with the ex situ conservation and management of forest genetic resources. It outlines the role of ex situ conservation and reviews some of the strategies that may be employed, the managed development of the ex situ populations, as well as methods for storage, in the field and in seed banks, for ex situ genetic resources. With volumes 1 and 2, and with other publications that are also addressing forest gene conservation issues at regional levels, we hope we have been able to provide the users of these manuals with an integrated view of the conservation approaches that can be used for the management of forest genetic resources around the world.